Comprehensive quality assessment for aphasia rehabilitation after stroke: protocol for a multicentre, mixed-methods study - Monique F Kilkenny; Joosup Kim; Dominique A Cadilhac; Deborah Hersh; Erin Godecke; David A Copland; Kathryn Mainstone; Penelope Mainstone; Sarah J Wallace; Miranda L Rose; Sam Harvey; Marissa Stone; et al. (BMJ Open)
Introduction People with aphasia following stroke experience disproportionally poor outcomes, yet there is no comprehensive approach to measuring the quality of aphasia services. The Meaningful Evaluation of Aphasia SeRvicES (MEASuRES) minimum dataset was developed in partnership with people with lived experience of aphasia, clinicians and researchers to address this gap. It comprises sociodemographic characteristics, quality indicators, treatment descriptors and outcome measurement instruments. We present a protocol to pilot the MEASuRES minimum dataset in clinical practice, describe the factors that hinder or support implementation and determine meaningful thresholds of clinical change for core outcome measurement instruments.Methods and analysis This research aims to deliver a comprehensive quality assessment toolkit for poststroke aphasia services in four studies. A multicentre pilot study (study 1) will test the administration of the MEASuRES minimum dataset within five Australian health services. An embedded mixed-methods process evaluation (study 2) will evaluate the performance of the minimum dataset and explore its clinical applicability. A consensus study (study 3) will establish consumer-informed thresholds of meaningful change on core aphasia outcome constructs, which will then be used to establish minimal important change values for corresponding core outcome measurement instruments (study 4).Ethics and dissemination Studies 1 and 2 have been registered with the Australian and New Zealand Clinical Trial Registry (ACTRN12623001313628). Ethics approval has been obtained from the Royal Brisbane and Women’s Hospital (HREC/2023/MNHB/95293) and The University of Queensland (2022/HE001946 and 2023/HE001175). Study findings will be disseminated through peer-reviewed publications, conference presentations and engagement with relevant stakeholders including healthcare providers, policy-makers, stroke and rehabilitation audit and clinical quality registry custodians, consumer support organisations, and individuals with aphasia and their families.